The application of a monolithic triphenylphosphine reagent for conducting Appel reactions in flow microreactors - Roper, Kimberley A.; Lange, Heiko; Polyzos, Anastasios; Berry, Malcolm B.; Baxendale, Ian R.; Ley, Steven V. (Beilstein Journal of Organic Chemistry, 2011)
Herein we describe the application of a monolithic triphenylphosphine reagent to the Appel reaction in flow-chemistry processing, to generate various brominated products with high purity and in excellent yields, and with no requirement for further off-line purification.
Keywords: Appel reaction; bromination; flow chemistry; solid-supported reagent; triphenylphosphine monolith

(untitled) - Wenger, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Webb, D.; Jamison, T. F. (Chem. Sci., 2010)

Microreactors in Organic Synthesis and Catalysis - Baxendale, I. R.; Hayward, J. J.; Lanners, S.; Ley, S. V.; Smith, C. D. (Heterogeneous Reactions, 2008)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V. (Mol. Diversity, 2011)

(untitled) - Ahmed-Omer, B.; Brandt, J. C.; Wirth, T. (Org. Biomol. Chem., 2007)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Smith, C. D.; Tranmer, G. K. (Org. Lett., 2006)

New Avenues to Efficient Chemical Synthesis: Emerging Technologies. Ernst Schering Foundation Symposium Proceedings 06.3 - Baxendale, I. R.; Ley, S. V. (Solid Supported Reagents in Multi-Step Flow Synthesis, 2007)

(untitled) - Hodge, P. (Ind. Eng. Chem. Res., 2005)

(untitled) - Kirschning, A.; Solodenko, W.; Mennecke, K. (Chem.–Eur. J., 2006)

(untitled) - Baxendale, I. R.; Deeley, J.; Griffiths-Jones, C. M.; Ley, S. V.; Saaby, S.; Tranmer, G. K. (Chem. Commun., 2006)

(untitled) - Baxendale, I. R.; Griffiths-Jones, C. M.; Ley, S. V.; Tranmer, G. K. (Synlett, 2006)

(untitled) - Ley, S. V.; Baxendale, I. R.; Bream, R. N.; Jackson, P. S.; Leach, A. G.; Longbottom, D. A.; Nesi, M.; Scott, J. S.; Storer, R. I.; Taylor, S. J. (J. Chem. Soc., Perkin Trans. 1, 2000)

Monolithic Materials: Preparation, Properties and Applications - Švec, F.; Tennikova, T. B. (Historical Review, 2003)

Monolithic Materials: Preparation, Properties and Applications - Švec, F.; Fréchet, J. M. J. (Rigid Macroporous Organic Polymer Monoliths Prepared by Free Radical Polymerization, 2003)

(untitled) - Buchmeiser, M. R. (Polymer, 2007)

(untitled) - Svec, F.; Fréchet, J. M. J. (Science, 1996)

(untitled) - Kunz, U.; Kirschning, A.; Wen, H.-L.; Solodenko, W.; Cecilia, R.; Kappe, C. O.; Turek, T. (Catal. Today, 2005)

(untitled) - Peters, E. C.; Svec, F.; Fréchet, J. M. J. (Adv. Mater., 1999)

(untitled) - Svec, F.; Fréchet, J. M. (J. Anal. Chem., 1992)

(untitled) - Lange, H.; Capener, M. J.; Jones, A. X.; Smith, C. J.; Nikbin, N.; Baxendale, I. R.; Ley, S. V. (Synlett, 2011)

(untitled) - Baumann, M.; Baxendale, I. R.; Kirschning, A.; Ley, S. V.; Wegner, J. (Heterocycles, 2011)

(untitled) - Baumann, M.; Baxendale, I. R.; Martin, L. J.; Ley, S. V. (Tetrahedron, 2009)

(untitled) - Mennecke, K.; Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Baumann, M.; Baxendale, I. R.; Ley, S. V.; Nikbin, N.; Smith, C. D. (Org. Biomol. Chem., 2008)

(untitled) - Nikbin, N.; Ladlow, M.; Ley, S. V. (Org. Process Res. Dev., 2007)

(untitled) - Altava, B.; Burguete, M. I.; García-Verdugo, E.; Luis, S. V.; Vicent, M. J. (Green Chem., 2006)

(untitled) - Kirschning, A.; Altwicker, C.; Dräger, G.; Harders, J.; Hoffmann, N.; Hoffmann, U.; Schönfeld, H.; Solodenko, W.; Kunz, U. (Angew. Chem., Int. Ed., 2001)

(untitled) - Solodenko, W.; Wen, H.; Leue, S.; Stuhlmann, F.; Sourkouni-Argirusi, G.; Jas, G.; Schönfeld, H.; Kunz, U.; Kirschning, A. (Eur. J. Org. Chem., 2004)

(untitled) - Kunz, U.; Schönfeld, H.; Kirschning, A.; Solodenko, W. (J. Chromatogr., A, 2003)

(untitled) - Burguete, M. I.; García-Verdugo, E.; Vicent, M. J.; Luis, S. V.; Pennemann, H.; Graf von Keyserling, N.; Martens, J. (Org. Lett., 2002)

(untitled) - Tripp, J. A.; Stein, J. A.; Svec, F.; Fréchet, J. M. J. (Org. Lett., 2000)

(untitled) - Smith, C. J.; Smith, C. D.; Nikbin, N.; Ley, S. V.; Baxendale, I. R. (Org. Biomol. Chem., 2011)

(untitled) - Smith, C. J.; Nikbin, N.; Ley, S. V.; Lange, H.; Baxendale, I. R. (Org. Biomol. Chem., 2011)

(untitled) - Desai, N. B.; McKelvie, N.; Ramirez, F. (J. Am. Chem. Soc., 1962)

(untitled) - Appel, R. (Angew. Chem., Int. Ed. Engl., 1975)

(untitled) - Choi, M. K. W.; He, H. S.; Toy, P. H. (J. Org. Chem., 2003)

(untitled) - Anilkumar, G.; Nambu, H.; Kita, Y. (Org. Process Res. Dev., 2002)

(untitled) - Årstad, E.; Barrett, A. G. M.; Hopkins, B. T.; Köbberling, J. (Org. Lett., 2002)

(untitled) - Harrison, C. R.; Hodge, P. (J. Chem. Soc., Chem. Commun., 1978)

(untitled) - Harrison, C. R.; Hodge, P.; Hunt, B. J.; Khoshdel, E.; Richardson, G. (J. Org. Chem., 1983)

(untitled) - Hodge, P.; Khoshdel, E. (J. Chem. Soc., Perkin Trans. 1, 1984)

(untitled) - Sherrington, D. C.; Craig, D. J.; Dagleish, J.; Domin, G.; Taylor, J.; Meehan, G. V. (Eur. Polym. J., 1977)

(untitled) - Tömöskozi, I.; Gruber, L.; Radics, L. (Tetrahedron Lett., 1975)

Polymeric Materials Encyclopedia - Sanchez, J.; Myers, T. N. (Peroxide Initiators (overview), 1996)
See for half-life information for dibenzyol peroxide.

(untitled) - de la Fuente, G. F.; Huheey, J. E. (Phosphorus, Sulfur Silicon Relat. Elem., 1993)

(untitled) - Hornung, C. H.; Mackley, M. C.; Baxendale, I. R.; Ley, S. V. (Org. Process Res. Dev., 2007)

(untitled) - He, P.; Haswell, S. J.; Fletcher, P. D. I. (Sens. Actuators, B, 2005)